2019
DOI: 10.2106/jbjs.18.01114
|View full text |Cite
|
Sign up to set email alerts
|

The Personal Financial Burden Associated with Musculoskeletal Trauma

Abstract: Background: Little is known about the effect of orthopaedic trauma on the financial health of patients. We hypothesized that some patients who sustain musculoskeletal trauma experience considerable financial hardship during treatment, and we also assessed for factors associated with increased personal financial burden. Methods: We surveyed 236 of 393 consecutive patients who were approached at 1 of 2 American College of Surgeons level-I trauma centers b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 21 publications
2
37
2
Order By: Relevance
“…Given that most patients completed PT outside of our system, we were also limited in our ability to evaluate beyond duration and visit number, including important objective return-to-play metrics. Fifth, our sample size was limited by the number of isolated ACLRs performed at our institution, but our survey response rate of 45% was similar to those of previous studies of the financial burden of orthopaedic care 14,15. Finally, we studied patients treated at 1 academic institution in 1 state, so our results may not be generalizable to hospitals with different safety net and disproportionate sharing statuses.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Given that most patients completed PT outside of our system, we were also limited in our ability to evaluate beyond duration and visit number, including important objective return-to-play metrics. Fifth, our sample size was limited by the number of isolated ACLRs performed at our institution, but our survey response rate of 45% was similar to those of previous studies of the financial burden of orthopaedic care 14,15. Finally, we studied patients treated at 1 academic institution in 1 state, so our results may not be generalizable to hospitals with different safety net and disproportionate sharing statuses.…”
Section: Discussionmentioning
confidence: 96%
“…Both are validated measures for assessment of financial hardship experienced with medical treatment 13. Both measures have been used to assess the financial burden associated with orthopaedic care in adults 14,15…”
Section: Methodsmentioning
confidence: 99%
“…26,27 One study found that a quarter of patients who experienced orthopaedic trauma had high financial distress, and nearly the same amount of patients needed to borrow money to pay for the costs, even though 97.9% of the sample had insurance. 28 Although indirect medical costs like transportation and lost time from paid work are more difficult to address, efforts to reduce costs in orthopaedic surgery could minimize a treatment's effect on financial distress. This study provides further evidence that nonoperative management leads to fewer complications in the elderly population.…”
Section: Discussionmentioning
confidence: 99%
“…In orthopaedic surgery, patients have been shown to postpone visits and have higher levels of subjective disability as a result of financial distress 26,27. One study found that a quarter of patients who experienced orthopaedic trauma had high financial distress, and nearly the same amount of patients needed to borrow money to pay for the costs, even though 97.9% of the sample had insurance 28. Although indirect medical costs like transportation and lost time from paid work are more difficult to address, efforts to reduce costs in orthopaedic surgery could minimize a treatment’s effect on financial distress.…”
Section: Discussionmentioning
confidence: 99%
“…In Massachusetts, recent health reforms led to an increased number of insured individuals [ 3 , 4 ]. However, even among insured patients, the amount of financial burden caused by medical expenditures varies considerably [ 5 ]. When considering treatment adherence after unexpected musculoskeletal trauma, financial burden is especially important as medical expenses may prevent low-income populations from accessing follow-up services.…”
Section: Introductionmentioning
confidence: 99%